Agustín de Salazar y Torres, Elegir al enemigo. Ed. Thomas Austin O'Connor. Global PUblications-Binghamton University, New York, 2002; 143 pp. - Alatorre, Antonio (El Colegio de México, 2004)
Se reseñó el libro: Elegir al enemigo.